Gut microbiota alteration and its association with immune function in post-COVID-19 patients - Cai, Jiaojiao; Xu, Jingru; Tan, Yan; Xiang, Yao; Li, Zhifeng; Zheng, Juan; Li, Yingli (Folia microbiologica, 2024)
To reveal the variation of gut microbiota and its association with immune function in cured patients with coronavirus 2019 (COVID-19) disease, gut microbiota of patients discharged from hospital for 20 ~ 23 months and healthy volunteers was analyzed by high throughput 16S rRNA sequencing. The diversity and abundance were compared, and the correlation with immunity factors was investigated, and changes in the content of 6 genera microorganisms with proportion higher than 0.1% were revealed in patients with COVID-19 disease: reduced content of Subdoligranulum, Haemophilus, Coprococcus, Eubacterium vertriosum group, and Lachnospiraceae ND3007 group and increased content of Hungatella. NK cells were negatively correlated to Subdoligranulum, while CD8 cells were positively correlated to Subdoligranulum but negative to Hungatella. IL-8 concentration was negatively correlated to Subdoligranulum, Haemophilus, Coprococcus, Eubacterium vertriosum group, and Lachnospiraceae ND3007 group but positively to Hungatella, while IL-1β concentration was negatively correlated to Haemophilus and Eubacterium ventriosum group but positively to Hungatella. The variation of probiotics and potential pathogenic bacteria implies a higher risk in diseases and inflammation, and the modulation of the gut microbiota may help the healing of COVID-19 patients.
Keywords: dospělí; Female; feces; SARS-CoV-2; Feces; Immune function; Interleukin-8; Adult; ženské pohlaví; Gastrointestinal Microbiome; buňky NK; RNA, Ribosomal, 16S; 16S rRNA; lidé; COVID-19; interleukin-8; Variation; Interleukin-1beta; Male; Aged; Bacteria; střevní mikroflóra; Killer Cells, Natural; interleukin-1beta; Gut microbiota; lidé středního věku; senioři; mužské pohlaví; Middle Aged; RNA ribozomální 16S; Humans